PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN MENULIS DESKRIPSI PADA SISWA TUNARUNGU DI SEKOLAH LUAR BIASA - DARMAYANTI, ALFINA (Jurnal Pendidikan Khusus, 2017)
ABSTRACT:Hearing impairment caused the obstruction of speech ability which produced complex development problem. Inhibition of language development includes aspects of listening, speaking, reading which result in writing skills. Therefore, it takes learning that helps the child in writing with attention to the characteristics of the child. The scientific approach is a learning process that encourages students to perform scientific activities by observing, questioning, gathering information and communicating. A scientific approach was learning approach giving priority to Visual senses that match the characteristics of deaf students who tend to optimize their sense of view to capture information. This research had purpose to analyze the influence of scientific approach in learning writing description. This research uses quantitative approach and pre experimental research type. The research design "One Group, pretest-posttest design" with the subject of research of children with hearing impairment class II which amounted to 6 people. Location of research at SLB Muhammadiyah Sidayu Gresik. The method of data collection used test and the technique of data analysis used statistic non parametric with sign test. Based on the data analysis it indicated ZH = 2,05> Z table = 1,96 to 5% significant level (two sides test). So, it could be concluded that there was significant influence of scientific approach toward writing description ability to hearing impairment students of class II in SLB Muhammadiyah Sidayu.   Keywords: Scientific Approach, Writing Learning